2010
DOI: 10.1074/jbc.m110.164525
|View full text |Cite
|
Sign up to set email alerts
|

Ablation of Skeletal Muscle Triadin Impairs FKBP12/RyR1 Channel Interactions Essential for Maintaining Resting Cytoplasmic Ca2+

Abstract: ] rest in triadin-null myotubes is primarily driven by dysregulated RyR1 channel activity that results in part from impaired FKBP12/RyR1 functional interactions and a secondary increased Ca 2؉ entry at rest.In skeletal muscle, where control of cytosolic Ca 2ϩ concentration is key to muscle contraction, the overall Ca 2ϩ homeostasis is preserved by a concerted action of several ionic channels and transporters within the plasma membrane and the sarcoplasmic reticulum (SR).3 These proteins, including plasma membr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
43
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(50 citation statements)
references
References 37 publications
7
43
0
Order By: Relevance
“…In an apparent disagreement with our results Oddoux et al [12] reported no statistical differences in RyR1 expression between Wt and triadin KO muscles, a difference that could be related to a higher dispersion in densitometric data in Oddoux’s report. As reported previously [13], expression of FKBP12 was also up-regulated in Tdn-null myotubes to 216 ± 21% of the Wt expression levels.…”
Section: -Results and Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…In an apparent disagreement with our results Oddoux et al [12] reported no statistical differences in RyR1 expression between Wt and triadin KO muscles, a difference that could be related to a higher dispersion in densitometric data in Oddoux’s report. As reported previously [13], expression of FKBP12 was also up-regulated in Tdn-null myotubes to 216 ± 21% of the Wt expression levels.…”
Section: -Results and Discussionsupporting
confidence: 86%
“…Instead, an impairment of either the allosteric transmission of the orthograde signal to RyR1 or RyR1-mediated Ca 2+ release itself seem more feasible. In this regard, our previous studies have shown that both a significant disruption FKBP12/RyR1 interaction and a sizable reduction in SR Ca 2+ content are associated with triadin ablation [13] and either of these effects by itself could account for the reduction in amplitude of the Ca 2+ release signal seen in triadin-null myotubes.…”
Section: -Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar findings were shown in isolated myotubes from the same mice as well as a significant increase in resting myoplasmic Ca ++ [131]. In support, Eltit et al (2010) demonstrated chronically elevated resting myoplasmic Ca ++ due to FKBP12-RyR1 dysfunction and SR store-operated Ca ++ entry [52, 53], suggesting increased basal RyR1 activity in triadin null myotubes isolated from skeletal muscle of mice. Additionally, Oddoux et al (2009) revealed a reduction of SR Ca ++ .…”
Section: Introductionsupporting
confidence: 53%
“…A number of studies have identified that triadin is “primarily a negative regulator of RyR1 [52]” [68, 70, 103, 131]. One study showed that amino acids 664 to 799 of DHPR alpha 1 subunit bind to triadin primarily at amino acids 68–278 [58].…”
Section: Introductionmentioning
confidence: 99%